Enantioselective Nickel-Catalysed Arylative and Alkenylative Cyclisations onto Electron-Deficient Alkenes via E/Z Isomerisation - Gillbard, Simone Marie (2023)
Herein is presented a highly enantioselective nickel-catalysed anti-carbometallative-cyclisation reaction of substrates containing an alkyne tethered to an electron-deficient alkene. Enantioenriched cyclopentene products, that are otherwise difficult to synthesise, are obtained in up to 99% yield and >99% ee. The overall anti-carbometalation of the alkyne is enabled by the critical reversible E/Z isomerisation of alkenylnickel intermediates. Investigation of the substrate scope revealed that alkyne substituents such as (hetero)aryl and alkenyl groups were compatible with the reaction and substrates containing electron-deficient alkenes such as α,β-unsaturated alkyl or (hetero)aryl ketones, nitroalkenes, α,β-unsaturated esters and alkenyl nitriles successfully participated in the reaction. Also, (hetero)arylboronic acid as well as alkenylboronic acids were tolerated in the reaction. Efforts were made towards the synthesis of enantioenriched 6-membered carbo- and heterocyclic products by extending the tether between the alkyne and the electron-deficient alkene in the substrate.